The Ability of Problem-based Learning (PBL) to Improve Problem-solving Skills on Heat Topic Among High School Students - Ekasari, Aprilita; Diantoro, Markus; ., Parno (KnE Social Sciences, 2023)
Problem-solving should be improved to support students’ competence in solving physics problems as well as problems that occur in daily life. The initial research showed that high school students in Tulungagung have low level of problem-solving skills at 41.2% and 39.4%, respectively. Therefore, this study aims to determine the improvement of the problem-solving skills among high school students at PGRI Kalangbret who had been taught problem-based learning on the topic of heat. This study used research design of mixed methods embedded experimental model. The subjects consisted of 30 students at class X MIPA. This research used quantitative analysis to analyze the effect size test, N-gain test, paired t-test, and qualitative with the help of coding and data reduction, from pretest, pottest, observation, and field notes. Based on the results, it was found that students’ problem-solving skill were improved after being taught with problem-based learning (PBL) on heat topic with an average N-gain score of 0.41; and effect size 1.66. Keywords: problem-based learning, problem-solving skills, high school